Upaya Meningkatkan Kapasitas Pengurus Masjid Dan Masyarakat Dalam Pengelolaan Serta Pemanfaatan Masjid Secara Optimal - Hariyanto, Nur; Harahap, Ali Usman; Pratama, Adit Tio; Firdaus, Wina Mukminatul; Widiyanti, Septi; Ulandari, Ulandari; Anisa, Sinta Karisma; Liani, Alfi; Veronika, Jesi; Zahara, Ristika; Sopa, Gita Maya (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) in Sekaian Village, Lubuk Sandi Subdistrict, Seluma Regency, is an initiative aimed at improving the quality of life for the villagers through a range of integrated programs. The students involved in this KKN focus on identifying local issues and implementing concrete solutions in the areas of education, health, economy, and environment. This activity is designed to empower the Sekaian Village community using a participatory approach that engages residents in every stage of program planning and implementation. The results of this KKN demonstrate that collaboration between students, village government, and the community can have a positive impact on the well-being of the villagers. Programs such as health education, skills training, and literacy enhancement successfully provided new knowledge and skills to the residents. Additionally, this KKN offered practical experience for students in applying the knowledge they have acquired in college to real-life situations, while also fostering social awareness and a sense of responsibility towards the community.